Study of the inulin complex of dahlia root bulbs of Ken's flame species and its standardization - Ilyinska, Nonna; Gontova, Tetiana; Chushenko, Valentina; Bezugly, Petro (ScienceRise: Pharmaceutical Science, 2017)
The literature data analysis has shown that phytopolysaccharides are perspective sources for study and development of active pharmaceutical ingredients, and can be used as new medicines or biologically active additives in future. Therefore, the obtained polysaccharide complex from the root bulbs of Dahlias “Ken's Flame” species is perspective for the further research and isolation of new pharmaceutical ingredients and substances. Methods. The polysaccharide complex was obtained from the Dahlia’s tubers of “Ken's Flame” species. Paper chromatography method was used to identify monosaccharides of the polysaccharide complex. Quantitative determination of fructose in the complex was carried out by adsorption spectrophotometry using α-naphthol. Results. Fructose and glucose were identified by standard paper chromatography after acidic hydrolysis of the polysaccharide complex in selected standard conditions. For the quantitative determination of fructose, the Dyshe reaction was used: with α-naphthol in acidic medium. The influence of boric acid and urea supplements on the optical absorption of fructose and glucose in the given reaction was studied. The polysaccharide complex hydrolysis kinetics was studied; conditions for reaction of fructose with α-naphthol in acidic medium were selected. Conclusions. The standard conditions for the hydrolysis of the inulin complex were determined, followed by the identification of monosaccharides: fructose and glucose by paper chromatography method. The method of determination of fructose with α-naphthol in acidic medium for a polysaccharide complex obtained from the Dahlia’s tubers of “Ken's Flame” species was developed. Experimental studies devoted to the inulin complex (IC) identification using chromatography, determined conditions for the reaction of fructose with α-naphthol in acidic medium, as well as conditions for IC hydrolysis, and IC standardization are presented in the article